Photocatalytic Evaluation of Anatase TiO2 Coating on Ceramic Tiles by Raman Spectroscopy. Issue 1 (2nd January 2020) - Medda, Samar Kumar; Manna, Srikrishna; De, Goutam
Abstract: The present work reports a convenient way to evaluate the photocatalytic activity of anatase TiO2 films by monitoring the degradation of methylene blue (MB) directly on the TiO2 coated tiles under simulated solar light (1 sun condition; AM 1.5G simulator) using Raman spectroscopy. For this purpose, nanocrystalline TiO2 films of aesthetic quality (thickness ∼80±5 nm) were deposited by the sol-gel method on the glazed tiles. XRD and Raman studies of the calcined coatings (500°C/2 h in air) confirmed the formation of anatase phase of TiO2 . The water contact angle (θ) value of the coated tiles was found to be 20±1° (hydrophilic) and no significant change of θ was noticed after storing in ambient condition for 3 months. The MB decomposition on the TiO2 coating under 1 sun condition was monitored by recording the Raman spectra with respect to time. Using this technique, the apparent rate constant (kapp ) value of MB degradation was found to be 0.2554 min −1 . The total photo-decomposition of dye and its repeatability studies through direct Raman monitoring of the coating surface ensured the self-cleaning ability of the TiO2 coatings. GRAPHICAL ABSTRACT: